THE EFFECT OF ADDING SEA CUCUMBER (Holothuria scabra) PROTEIN CONCENTRATE ON THE QUALITY CHARACTERISTICS OF THE BISCUITS - Miftakul Amin; Desmelati Desmelati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study aims to determine the effect of adding protein concentrate of sea cucumber (Holothuria scabra) and determine the best amount of concentration in producing biscuit quality through an organoleptic and chemical test. The research method was experimental by adding protein concentrate to sea cucumber in different concentrations. The research designed in Completely Randomized Design (CRD) consisting of 4 levels of treatment, namely without the addition of 0% (B0) sea cucumber protein concentrate, 5% (B1), 10% (B2), and 15% (B2) of sea cucumber protein concentrate 5% (B3). The best parameters were on organoleptic test and chemical analysis (moisture, ash, fat, protein, carbohydrate content). The results showed that the addition of sea cucumber protein concentrates affected the quality of the biscuits, the best quality of biscuits was obtained from the use of sea cucumber protein concentrate 5% (14 grams), with the characteristics of brownish-yellow biscuits, distinctive aroma of biscuits, dry and brittle texture, and a crunchy taste, and sweet. Sea cucumber protein concentrate biscuits have a moisture content of 3.76%, 1.75% ash, 9.26% protein, 23.47% fat, and 61.76% carbohydrates. Keywords: biscuits, protein concentrate, sea cucumber